Chad : Enhanced Heavily Indebted Poor Countries Initiative-Completion Point Document and Multilateral Debt Relief Initiative. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses the status of Chad under Enhanced Heavily Indebted Poor Countries (HIPC) Initiative and Multilateral Debt Relief Initiative (MDRI). Chad does not qualify for topping-up under the Enhanced HIPC Initiative based on end-2013 debt data. Creditors accounting for more than 87 percent of total HIPC-eligible debt have given satisfactory assurances of their participation in the enhanced HIPC Initiative. Nearly all multilateral creditors and Paris Club creditors have agreed to participate. The authorities are working toward obtaining participation of all the remaining creditors. Upon reaching the completion point under the Enhanced HIPC Initiative, Chad will also qualify for additional debt relief under the MDRI.